Spatiotemporal spatfall dynamics and prevailing estuarine conditions for optimal oyster (Crassostrea tulipa) spat availability in selected Gulf of Guinea brackish systems - Chuku, Ernest Obeng; Yankson, Kobina; Obodai, Edward Adzesiwor; Acheampong, Emmanuel; Aheto, Denis Worlanyo (Frontiers in Marine Science, 2023)
Uncertainties associated with wild harvests of seed and adult oysters due to unknown oceanographic oscillations are a major challenge in oyster fisheries and aquaculture development. In contribution to addressing this challenge, we proffer clarity on the spatiotemporal variations in spatfall (number of spat/m2) of the mangrove oyster Crassostrea tulipa (Lamarck, 1819) in four estuaries along the Gulf of Guinea coast. By monthly deployment of artificial substrates affixed to bamboo racks over 12 months, we find significant differences in spatfall among and within the brackish systems, and across months and seasons. Spatfall regimes were unique in each ecosystem albeit with an overall preponderance of dry season availability of spat. Locations with reef oysters had superior spatfall to mangrove root-adapted-oyster areas. Narkwa, a relatively small lagoon with reef oysters had the highest annual mean spatfall, which was 1.3, 2.5, and 9.8 folds the spatfall in Densu Delta, Benya Lagoon and Whin Estuary, respectively. Spatfall varied significantly by depth as the more frequently exposed top collectors harvested much less spat than submerged collectors. There was a year-round availability of spat, confirming continuous spawning in C. tulipa. Spatfall variability was significantly driven by fluctuations in prevailing dissolved oxygen and salinity. Prevailing dissolved oxygen and salinity levels in the estuaries for optimal spat settlement were 1.68 – 3.40 mg L-1 and 11.00 – 29.33 ppt (parts per thousand), respectively. The findings of this study are recommended as empirical reference points for sustainable seed procurement for aquaculture production and management of C. tulipa fishery in the region of the study.